PENGEMBANGAN RENCANA PELAKSANAAN PEMBELAJARAN MENGGUNAKAN JIGSAW BERBASIS KARAKTER UNTUK MENINGKATKAN AKTIVITAS MAHASISWA - Setya Ferywidyastuti (Universitas Muhammadiyah Semarang, 2015)
The purpose of this research is to develop lesson plan of Optical Physics material using jigsaw technique to increase students’ activities. The research used R&D model using True Experimental Design with pretest-posttest control group design. The subject were determined through random sampling techniques, namely Student Semester II as a control class and the Student Semester IV as the experimental class in Optic Refraction Study Program (RO) STIKES HAKLI Semarang year 2014/2015. Data collection techniques using validation sheet, student activity observation sheet and questionnaire sheet. The validity of the results of the validation indicated that the average score of validation RPP 52 (maximum score 60) as a very good category. The effectiveness of the test results are: (1) the test results of students' experimental class achieve mastery with an average of 79.06 with the percentage of students who got score standard 86.11%, (2) the development of lesson plan can enhance the activity of students with criteria score 3.4 that was including very active and the impact of activity-based character education students in the learning process of the students' learning outcomes about 43.68%. Practicality can be seen with the results of student responses 90.3% who pleased in follow learning process.Keywords : lesson plan development, jigsaw, character